Endometrial Cancer Cells Promote M2-Like Macrophage Polarization by Delivering Exosomal miRNA-21 under Hypoxia Condition. (13th October 2020) - Xiao, Li; He, Yumin; Peng, Fan; Yang, Jianlin; Yuan, Chengfu
Abstract : Increasing evidence has demonstrated that hypoxia was an aggressive feature in endometrial cancer (EC), which is significantly associated with the tumor grade, lymph node metastasis, and tumor resistance to chemotherapy. However, the relationship between hypoxia and the immune microenvironment in EC is not very clear. Exosomes are small membrane vesicles secreted from a variety of cell types which mediate cell-to-cell communication through transported biomolecules. Here, we investigated whether exosomes can play an immunomodulatory role in intercellular communication between EC cells and macrophages. EC KEL cells were cultured under hypoxia or normoxic condition to collect exosomes. After identification, the exosomes derived from hypoxic or normoxic KEL cells were cultured with the monocyte cell line THP-1 to study the immunoregulation function of KEL cells. The results showed that the total number of exosomes produced by hypoxic KEL cells was significantly higher than that in normoxic condition. In addition, hypoxia markedly stimulated the increase in miRNA-21 expression in the exosomes. After coculture, we found that exosomal miRNA-21 could be horizontally transferred into THP-1 cells. And then, the notably enhanced mRNA expression levels of IL-10 and CD206 in THP-1 cells were observed, suggestive of M2 polarization. To further study the effect of miRNA-21-containing exosomes, we transfected miRNA-21 mimics or inhibitor into THP-1 cells. The results showed that miRNA-21 mimics promoted IL-10 and CD206 mRNA expression levels, and the miRNA-21 inhibitor significantly prevented the alteration induced by intake of hypoxic KEL cell-derived exosomes. In summary, we found that endometrial cancer KEL cells in hypoxic condition promoted monocyte THP-1 cell transformation to M2-like polarization macrophages through delivering exosomal miRNA-21, which may be a potential mechanism of the formation of the immune microenvironment in EC progression.